2017
DOI: 10.1515/amm-2017-0272
|View full text |Cite
|
Sign up to set email alerts
|

Influence of The Arrangement of Materials and Microstructural Analysis During FSW of AZ80A & AZ91C Mg Alloys

Abstract: The main objective of this paper is to produce defect free weldments with improved properties during friction stir welding of dissimilar Mg alloys. The influence of the anisotropic arrangement of materials when AZ80A Mg alloy is taken as advancing side and AZ91C Mg alloy as retreating side and vice versa with respect to their mechanical properties and microstructural characteristics were investigated. The effects of various FSW parameters on the quality of these joints were also analyzed and best optimized FSW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…It is one of the oldest and popular methods of metal cutting. It has even replaced grinding in several applications with reduced lead time without affecting the surface quality [21][22][23][24]. In this investigation; the experiments were carried out on a rigid CNC machine with spindle speed of 2500rpm.…”
Section: Methodsmentioning
confidence: 99%
“…It is one of the oldest and popular methods of metal cutting. It has even replaced grinding in several applications with reduced lead time without affecting the surface quality [21][22][23][24]. In this investigation; the experiments were carried out on a rigid CNC machine with spindle speed of 2500rpm.…”
Section: Methodsmentioning
confidence: 99%
“…In FSW, the rotating tool having specially designed pin [21] inserted into the abutting edges of workpiece and traversed to produce the joint [22]. During welding, the frictional heat, produced between the rotating tool surface and the surface of the metal sheet, is responsible for the plastic deformation of the workpiece material [22,23]. This localised heat softens the material around the tool pin.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, AZ91 magnesium alloys have chosen due to its better industrial importance. Earlier, Kadigithala and Vanitha [27], Lee et al [28], and Kouadri-Henni and Barrallier [29] have studied friction stir welded joint of AZ91D magnesium alloy and observed mechanical and microstructural modifications in the various zones of the weld joint whereas, Rouhi et al [30] and Sevvel and Jaiganesh [23] have reported the FSW joining of AZ91C Mg alloys. Some researchers including Patel et al [31], Zhang and Wan [32] and Nakata [33] also ABSTRACT -The weight reduction concept is most effective to reduce the emissions of greenhouse gases from vehicles, which also improves fuel efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…A rotating FSW tool, non consumable in nature, along with a pin and shoulder profile navigates in between the regions of the parent metal to be joined. When the FSW tool travels along the joint area, due to the friction between the FSW tool shoulder surface and the parent metal surface, heat is generated [6][7][8][9][10]. Apart from this, this FSW tool also leads to plastic deformation at the location of the joints, thereby enabling the joining of the parent metals, even when they are in the solid state.…”
Section: Introductionmentioning
confidence: 99%